The effect of erythromycin and clarithromycin versus azithromycin on serum valproate concentration - Muradi Albanji; Samah Alshehri; Khalid Eljaaly (Elsevier, 2022)
Introduction: Unlike azithromycin, erythromycin and clarithromycin strongly inhibit CYP450, which metabolizes valproic acid. The aim of this study was to evaluate the impact of macrolide administration on serum valproate trough levels. Methods: This retrospective cohort study included hospitalized adult patients who concomitantly received valproate with a macrolide. Patients who received a carbapenem, those who do not have a baseline and/or post-levels, and those who received different doses of valproate were excluded. The change in serum valproate trough level from baseline to after the occurrence of co-administration (post-level) was compared in patients who received either erythromycin or clarithromycin versus those who received azithromycin. Results: A total of thirteen patients were included in the comparison. The mean ± SD for change in serum valproate trough levels was significantly higher in the erythromycin/clarithromycin group than the azithromycin group (209.1 ± 105.9 µmol/L [equivalent to 30.1 ± 15.2 mg/L] vs. 12.7 ± 52.1 µmol/L [equivalent to 1.8 ± 7.5 mg/L]; P = 0.002). Conclusion: This study found a significantly higher increase in serum trough levels of valproate after co-administration of erythromycin/clarithromycin versus azithromycin. Clinicians should consider avoiding co-administration of erythromycin and clarithromycin with valproate if possible or close monitoring of valproate levels with dose reduction.